Traction electric drive of locomotives with a group drive of wheel pairs - Roi, Serhii (National Technical University "Kharkiv Polytechnic Institute", 2024)
Choice of the drive of wheel pairs type was analyzed and it was established that the use of a group drive of wheel pairs provides the possibility of realizing high traction forces without additional devices, while the drive itself has a lower cost. This determines the expediency of using a group drive of wheel pairs when modernizing diesel locomotives with hydraulic power transmission.
Keywords: traction electric drive; rolling stock; locomotives; efficiency; modernizing diesel locomotives; wheel pairs